Strategi manajemen risiko dalam optimalisasi aplikasi e-commerce Cook Link - Kusnadi, Deky; Kustiawan, Unggul; Hamdi, Edi; Indradewa, Rhian (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2025)
Risk management is a crucial element in maintaining the sustainability of company operations, especially in the technology and application-based services industry. This research aims to analyze and develop risk mitigation strategies in Cook Link operations by applying the ISO 31000-based risk management framework. In addition, it evaluates the effectiveness of the strategy in improving supplier reliability, price transparency, and raw material supply chain efficiency for the hospitality industry. Using qualitative methods, this research follows the five stages of ISO 31000:2018, namely determining context, assessment, risk treatment, communication and consultation, and monitoring and review. The results show that Cook Link faces risks in operational, financial, technological and reputational aspects, which are categorized based on their likelihood and impact. To address these risks, the company implemented data-driven mitigation strategies through the Risk Matrix and Risk Treatment Plan, as well as effective risk communication using the RACI Matrix. This study confirms that the implementation of strategic and international standards-based risk management can improve business resilience, operational efficiency and customer confidence in Cook Link's services.